Tube Duodenostomy in Traumatic Duodenal Injuries - Muhammad Ateeq, Shazia Jehan, Muhammad Akram, Faisal G Bhopal (Journal of Rawalpindi Medical College, 2010)
Background: Duodenal injury is an uncommon injury but is associated with significant morbidity and mortality Methods: In this descriptive study, 67 patients with duodenal injury were studied. Surgical algorithms were adopted in accordance with the grade of duodenal injury. Results: The incidence of duodenal trauma was 3.1%. Age of the patients ranged from 15 to 70 years. Male to female ratio was 2.2:1. Gunshot wound (58.2%) was the commonest. Grade II injury (haematoma and laceration, involving more than one portion of duodenum) was seen in 29.85%. Majority (50.7%) were managed by primary repair and complex duodenal repair was performed in 11.94%. 88% had associated intraabdominal organ damage. Twenty three (34.3%) patients had haemorrhagic shock, five (7.4%) died peroperatively and overall mortality was 11.9%. Conclusion: Most of primary grade I and II duodenal injuries can be primarily repaired, whereas in grade III and IV complex injuries primary duodenal decompression with tube duodenostomy should be considered